SLC10A3 regulates ferroptosis of glioblastoma through the STAT3/GPX4 pathway - Qian Sun; Haoran Lu; Fan’en Yuan; Qingyu Zhao; Yuxin Wei; Ronggui Wang; Qianxue Chen; Baohui Liu (Scientific Reports)
Abstract Ferroptosis is closely related to disease progression and treatment response in human brain gliomas; however, the regulatory mechanisms involved remain to be elucidated. Identifying new ferroptosis regulatory factors holds promise for addressing the aberrant regulation of ferroptosis in glioblastoma (GBM) and overcoming its treatment resistance. In this research, bioinformatics revealed that SLC10A3 is upregulated in GBM and correlates with poor patient prognosis. Functional analysis showed that SLC10A3 regulates GBM growth and progression through ferroptosis and that silencing SLC10A3 enhances sensitivity to the ferroptosis inducer Erastin. Mechanistically, SLC10A3 modulates STAT3 transcription and phosphorylation, impacting GBM ferroptosis via the STAT3-GPX4 pathway, and the STAT3 phosphorylation inhibitor Stattic effectively reverses this process. In vivo experiments also demonstrated that silencing SLC10A3 effectively induces ferroptosis in GBM and inhibits GBM progression. Our findings may help elucidate the mechanisms behind GBM resistance and offer new potential therapeutic targets.